2021
DOI: 10.1126/sciadv.abc0671
|View full text |Cite
|
Sign up to set email alerts
|

Making climate projections conditional on historical observations

Abstract: Many studies have sought to constrain climate projections based on recent observations. Until recently, these constraints had limited impact, and projected warming ranges were driven primarily by model outputs. Here, we use the newest climate model ensemble, improved observations, and a new statistical method to narrow uncertainty on estimates of past and future human-induced warming. Cross-validation suggests that our method produces robust results and is not overconfident. We derive consistent observationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
189
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(237 citation statements)
references
References 48 publications
9
189
1
Order By: Relevance
“…These were averaged globally or separately over land and oceans for time series analysis (no correction for drift was performed) and regridded to a common 1 • grid by linear interpolation for pattern analysis. All figures of this paper are produced with the Earth System Model Evaluation Tool (ESMValTool) version 2.0 (v2.0) (Righi et al, 2020;Eyring et al, 2020;Lauer et al, 2020), a tool specifically designed to improve and facilitate the complex evaluation and analysis of CMIP models and ensembles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were averaged globally or separately over land and oceans for time series analysis (no correction for drift was performed) and regridded to a common 1 • grid by linear interpolation for pattern analysis. All figures of this paper are produced with the Earth System Model Evaluation Tool (ESMValTool) version 2.0 (v2.0) (Righi et al, 2020;Eyring et al, 2020;Lauer et al, 2020), a tool specifically designed to improve and facilitate the complex evaluation and analysis of CMIP models and ensembles.…”
Section: Resultsmentioning
confidence: 99%
“…A2) and CMIP6 (see Table A1) model output is available through the Earth System Grid Foundation (ESGF) and can be directly used within the ESM-ValTool (e.g., https://esgf-data.dkrz.de/projects/esgf-dkrz/, last access: 7 January 2021) (ESGF, 2021). The corresponding recipe that can be used to reproduce the figures of this paper will be included in ESMValTool v2.0 (Righi et al, 2020;Eyring et al, 2020;Lauer et al, 2020;Weigel et al, 2020) as soon as the paper is published. ESMValTool (v2.1) is released under the Apache License, VER-SION 2.0.…”
Section: Figure A8mentioning
confidence: 99%
“…The choice of stratospheric aerosol level specified in the CMIP6 preindustrial control simulations also has a substantial effect on comparisons between global warming relative to 1850 to 1900 in CMIP5 models and observations presented in the IPCC Special Report on 1.5 C ( 22 ). Additionally, this choice would influence attribution studies, which calculate scaling factors based on a comparison of simulated and observed temperature evolution since 1850 ( 23 25 ). If we are interested in making like-for-like comparisons of models and observations, then the most appropriate stratospheric aerosol background level would be what most closely approximates conditions over the previous several decades prior to the 1850 start of the historical simulation ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Historical trends in the UKCP18 methodology (Figure 1, labeled SAT) tend to reduce the upper tails of projected changes. Similarly, the HistC methodology (Brunner et al, 2020a section) is largely based on trend information, which also consistently downweights high end projected changes (Ribes et al, 2021), in response to too large change in such models over parts of the historical period.…”
Section: Contrasting and Combining Constraints From Different Methodologiesmentioning
confidence: 99%
“…Multiple techniques are available to constrain future projections drawing on different lines of evidence and considering different sources of uncertainty (e.g., Giorgi and Mearns, 2002;Knutti, 2010;Knutti et al, 2017;Sanderson et al, 2017;Lorenz et al, 2018;Brunner et al, 2020a,b;Ribes et al, 2021). Models that explore the full uncertainty in parameter space provide very wide uncertainty ranges (Stainforth, 2005), motivating the need to use observational constraints.…”
Section: Introductionmentioning
confidence: 99%